Analysis Of The Role And Effectiveness Of Qazwa Syariah Fintech In Financing Micro, Small And Medium Enterprises - Gianisa, Gianisa; Sahputri, Nabila; Azzahra, Najwa; Rajagukguk, Nesa Agatha Rose; Rahmadani, Rahmadani (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
This study analyzes the role and effectiveness of Qazwa sharia fintech in supporting Micro, Small, and Medium Enterprises (MSMEs) financing in Indonesia. Islamic fintech is developing as an alternative financing that encourages financial inclusion while still being based on Islamic principles, such as the prohibition of usury and the implementation of a profit-sharing system. This study aims to examine Qazwa's contribution in expanding MSME access to capital, assess the effectiveness of financing mechanisms, and assess its compliance with sharia principles. The research method uses a qualitative descriptive approach by collecting data through literature studies and non-participatory observation of the Qazwa platform's operations. The results of the study show that Qazwa plays an important role in increasing access to financing for MSMEs that have not been served by conventional financial institutions. The implementation of murabahah and mudharabah contracts increases transparency, builds trust between investors and business actors, and supports business sustainability. In addition, the use of digital processes such as electronic Know Your Customer (e-KYC) increases efficiency and accelerates the disbursement of funds, although there are still challenges related to Islamic financial literacy, regulation, and risk management.